A 3D-hydrodynamic model for predicting the environmental fate of chemical pollutants in Xiamen Bay, southeast China. (January 2020) - Ma, Liya; Lin, Bin-Le; Chen, Can; Horiguchi, Fumio; Eriguchi, Tomomi; Li, Yongyu; Wang, Xinhong
Abstract: Simulation model is very essential for predicting the environmental fate and the potential environmental consequences of chemical pollutants including those from accidental chemical spills. However very few of such simulation model is seen related to Chinese costal water body. As the first step toward our final goal to develop a simulation model for the prediction and the risk assessment of chemical pollutants in Chinese coastal water, this study developed a three-dimensional (3D) hydrodynamic model of Xiamen Bay (XMB). This hydrodynamic model was externally derived by meteorological data, river discharge and boundary conditions of XMB. We used the model to calculate the physical factors, especially water temperature, salinity and flow field, from June to September 2016 in XMB. The results demonstrated a good match between observations and simulations, which underscores the feasibility of this model in predicting the spatial-temporal concentration of chemical pollutants in the coastal water of XMB. Longitudinal salinity distributions and the mixing profile of river-sea interactions are discussed, including the obvious gradation of salinity from the river towards sea sites shown by the model. We further assumed that 1000 kg and 1000 mg/L of a virtual chemical pollutant leaked out from Jiulong River (JR) estuary (point source) and whole XMB (non-point source), respectively. The model illustrates that it takes three months for XMB to become purified when point source pollution occurs in the estuary, while half a year to be required in the case of non-point source pollution across the entire bay. Moreover, the model indicated that pollutants can easily accumulate in the western coastal zone and narrow waters like Maluan Bay, which can guide environmental protection strategies. Graphical abstract: Image 1 Highlights: Efficient monitoring of the chemical pollutants in the coastal water requires model simulations. The new hydrodynamic model allows for predicting the environmental fate of chemical pollutants in Xiamen Bay. Pollutant diffusion estimates point out the difficulties and priorities of environmental governance. The model largely improves the efficiency of the prevention, treatment and management of environmental contamination issues. To lay the foundation for future ecological evaluation and risk assessment.